Exploring the Viability of Waste Durian (Durio zibethinus) Seeds and Cempedak (Artocarpus integer) Seeds as Nutritive Resources: An Analytical Study of Their Suitability via Alcohol and Glucose Assays - Syarpin, Syarpin; Saputra, Rizki Rachmad; Haliza , Nur; Anista, Anista; Yanti, Helda; Sisilya, Tahsya Amanda; Fahmi, Rifaldi Lutfi (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2023)
Durian (Durio zibethinus) and Cempedak (Artocarpus integer), prominent staples in Indonesia, harbor seeds that can be harnessed for the production of 'Tapai', a traditional fermented product. This fermentation process within cempedak and durian seeds manifests in the generation of alcohol and glucose at discernible thresholds. Motivated by the prevalent underutilization of durian and cempedak seeds leading to wastage, this study aims to assess the viabilities of Tapai derived from these seeds by scrutinizing their alcohol and glucose profiles. Employing a quantitative descriptive approach, the research centers on cempedak and durian seed Tapais as the primary samples. Focusing on variables like alcohol and glucose content, the investigative technique incorporates distillation and titration using the Luff Schoorl method. Results are subsequently organized in frequency distribution tables following coding and tabulation. Observations reveal that alcohol and glucose levels in cempedak seed Tapai on the 10th day stand at 0.00% and 30.05%, respectively, while on the 15th day, they escalate to 4.88% and 41.92%. In the case of durian seed Tapai, levels on the 10th day are recorded at 4.88% for alcohol and 36.90% for glucose. On the 15th day, these figures rise to 16.57% for alcohol and 46.53% for glucose. Ultimately, this study underscores that the alcohol and glucose concentrations in cempedak and durian seed Tapais experience progressive augmentation over a 5-day period, rendering them safely consumable in moderate quantities.